Protein kinase associated with ribosomes phosphorylates ribosomal proteins of Streptomyces collinus - Mikulík, K; Janda, I (Biochemical and biophysical research communications, 1997)
Protein kinase activity associated with ribosomes of a kirromycin-producing strain of Streptomyces collinus was detected. The enzyme utilizes [gamma-32P]ATP to phosphorylate proteins, yielding acid-stable phosphoamino acids. Two-dimensional electrophoresis of proteins from a crude ribosomal fraction revealed 17 phosphoproteins. Eleven of the phosphoproteins exhibited electrophoretic mobility identical to that of S. collinus ribosomal proteins S3, S4, S12, S13, S14, S18, L2, L7, L16, L17, and L23. Protein L2 was identified by microsequencing of internal peptide fragments. Immunodetection with monoclonal antibodies indicated that the ribosomal proteins are phosphorylated on serine and threonine residues. Phosphorylation of ribosomal proteins led to the reduction of activity of ribosomes in the translation of poly(U). These results provide the first evidence of phosphorylation of ribosomal proteins in bacteriophage-uninfected cells of eubacteria.
Keywords: Electrophoresis, Gel, Two-Dimensional; Bacterial Proteins; Protein Kinases; proteinkinasy; Phosphorylation; 2D gelová elektroforéza; Streptomyces; Ribosomal Proteins; fosforylace; ribozomální proteiny; bakteriální proteiny; ribozomy; Ribosomes